2017
DOI: 10.1136/jmedgenet-2017-104521
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of mutations inPROSCas a novel cause of vitamin B6-dependent epilepsy

Abstract: Vitamin-B-dependent epilepsies are a heterogenous group of treatable disorders due to mutations in several genes ( or ). In neonatal seizures, defects in explain a major fraction of cases. Very recently biallelic mutations in were shown to be a novel cause in five families. We identified four further unrelated patients harbouring a total of six different mutations, including four novel disease mutations. Vitamin B plasma profiles on pyridoxine did not enable the differentiation of patients with mutations. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 8 publications
(19 reference statements)
1
53
1
Order By: Relevance
“…And, in cases with high clinical suspicion, mRNA studies 17 and testing for pyridoxine dependent seizure disorders should also be considered. 18,19 This study did not differentiate subjects in whom molecular testing was performed first as opposed to molecular testing performed after a diagnostic biochemical result.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…And, in cases with high clinical suspicion, mRNA studies 17 and testing for pyridoxine dependent seizure disorders should also be considered. 18,19 This study did not differentiate subjects in whom molecular testing was performed first as opposed to molecular testing performed after a diagnostic biochemical result.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, CNV analysis is important when only one pathogenic variant is identified, or in the case of a high clinical suspicion of PDE, even if no variants are identified through traditional sequencing methods. And, in cases with high clinical suspicion, mRNA studies and testing for pyridoxine dependent seizure disorders should also be considered . This study did not differentiate subjects in whom molecular testing was performed first as opposed to molecular testing performed after a diagnostic biochemical result.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tried to obtain evidence of a connection between PipY and the activity of PLP-holoenzymes, since a main consequence of COG0325 deficiency appears to be the low activity of PLP-holoenzymes (Darin et al, 2016; Prunetti et al, 2016; Plecko et al, 2017). To this end, we determined whether pipY inactivation affects the sensitivity to antibiotics targeting key PLP-holoenzymes such D -cycloserine (DCS) and β-chloro- D -alanine (BCDA), whose main target in bacteria is alanine racemase, an essential activity required for the synthesis of the cell wall (Feng and Barletta, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The pyridoxine sensitive phenotype of yggS null mutants could be complemented by heterologous expression of the plant and human COG0325 proteins, indicating that distantly related COG0325 proteins share common functions (Ito et al, 2013). Very recently, two different reports on human epilepsy (Darin et al, 2016; Plecko et al, 2017) confirmed the involvement of PROSC (the human COG0325 protein) in vitamin B6 homeostasis, showing that loss of function mutations at PROSC are a cause of vitamin B6-dependent epilepsy.…”
Section: Introductionmentioning
confidence: 97%
“…Prunetti et al reported that the yggS mutant of E. coli BW25113 accumulates PLP precursor pyridoxine 5=-phosphate (PNP) and is sensitive to excess levels of pyridoxine (PN) (3). Related to this finding, in humans, mutations in PROSC (ortholog of YggS) were identified as the cause of vitamin B 6 -dependent epilepsy (8,9). Analysis of cerebrospinal fluid samples from individuals possessing a PROSC mutation showed low PLP levels and reduced PLP-dependent enzyme activity.…”
mentioning
confidence: 99%